TRADITIONAL APPROACHES AND THE LATEST DEVELOPMENTS IN THE FIELD OF LIQUID FINISHING OF NATURAL LEATHER - ZAIETS, ANTONINA; ANDREYEVA, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The main trend in the development of the leather industry at present is the creation of high-quality competitive products while reducing environmental pollution, simplifying production processes, rational use of raw materials and material resources. At the same time, in modern methods of leather processing, there are still problems that make it difficult to achieve these prospects. This is largely due to the use of outdated processing techniques and insufficiently effective chemical materials.The production of natural leather is quite labor intensive, since it is carried out by sequentially performing a number of treatments from beamhouse and tanning to liquid and final finishing. After tanning, further formation of the structure and consumer properties of the leather, giving it an attractive presentation occurs during the liquid finishing. Due to the increasing spread of the production of Сrast, an uncoated semi-finished leather product, and the proposal of new methods for finishing the leather surface grain, the functions of liquid finishing are increasing. Therefore, in today's conditions, for the sustainable production of competitive leather materials, it is important to be aware of modern trends in improving the liquid finishing technology, fashion trends and the real needs of the consumer, which becomes possible through monitoring and implementation of modern developments, of course, taking into account the existing practical experience and established traditions.Based on the analysis of existing ideas and recent research in the field of fatliquoring, retanning and filling as the main processes of liquid finishing, the expediency of searching for and using more effective fatliquoring materials, especially modified ones, as well as new generation of polymer compounds, has been established. The belief in such expediency is based on the results of complex studies of the structure and properties of the investigated chemical and leather materials. The results obtained will be used in the development of a resource-saving environmentally oriented technology for the production of leather of a modern range.
Keywords: leather; liquid finishing; fatliquoring; retanning; filling; materials; properties